Tranexamic acid for haemostasis and beyond: does dose matter? - Tammy Lam; Robert L. Medcalf; Geoffrey C. Cloud; Paul S. Myles; Charithani B. Keragala (Thrombosis Journal, 2023)
Abstract Tranexamic acid (TXA) is a widely used antifibrinolytic agent that has been used since the 1960’s to reduce blood loss in various conditions. TXA is a lysine analogue that competes for the lysine binding sites in plasminogen and tissue-type plasminogen activator impairing its interaction with the exposed lysine residues on the fibrin surface. The presence of TXA therefore, impairs the plasminogen and tPA engagement and subsequent plasmin generation on the fibrin surface, protecting fibrin clot from proteolytic degradation. However, critical lysine binding sites for plasmin(ogen) also exist on other proteins and on various cell-surface receptors allowing plasmin to exert potent effects on other targets that are unrelated to classical fibrinolysis, notably in relation to immunity and inflammation. Indeed, TXA was reported to significantly reduce post-surgical infection rates in patients after cardiac surgery unrelated to its haemostatic effects. This has provided an impetus to consider TXA in other indications beyond inhibition of fibrinolysis. While there is extensive literature on the optimal dosage of TXA to reduce bleeding rates and transfusion needs, it remains to be determined if these dosages also apply to blocking the non-canonical effects of plasmin.